Analysis of Search Engine Optimization (SEO) Techniques - Jewliya, Shreekishan; Singh Rathore, Vikram (International Journal of Computer Sciences and Engineering, 2025)
website improvement is a deliberately procedure to take a web archive in top indexed lists of an internet searcher. Search engine optimisation (SEO) is a procedure of enhancing the conspicuousness of a site. This work depicts the changes of taking the page on top position in Google by expanding the Page rank which may bring about the enhanced perceivability and productive arrangement for an association. Google is most easy to use internet searcher demonstrated for the Indian clients which give client arranged outcomes more-over, the majority of other web indexes utilize Google look designs so we have focused on it. Along these lines, if a page is improved in Google it is streamlined for the greater part of the web search tools.